E-Resource Searcher (ERS) System - Chen, Liang (2010)
With the continue increase of the information, information retrieval (IR) has been becoming more important than ever before. Particularly in the digital library, generally it has a large plenty of E-Resource for the user to search and use. Therefore, this paper attempts to design an E-Resource searcher system which helps the student to find E-Resource faster and accurately among the ocean of E-Resource. The paper introduces the IR concepts, search engine working procedure, and the prominent open-source search library - Apache Lucene in details. The ERS search functionality primarily relies on the Lucene as full-text search core and partly depends on the traditional SQL query search for the common search. The research also presents feasible search architecture for the integration of the traditional database operation and search index database, which is appropriate for the most of the web-application embedded search. In addition, the IR (Information Retrieval) test collection is adopted to test the ERS search performances in precision and recall capabilities. The result is satisfactory and meets the research requirement.